Triagem virtual e síntese de dímeros de lapachol e isatina com potencial atividade antitumoral - Coelho, Maísa Cavalcanti (2019)
The cancer is a disease with a considerable impact on humanity. It is estimated that by 2018 it may have affected approximately 18.1 million people worldwide. In general, existing antitumor treatments presents high toxicity and reduce patient's quality of life, making it indispensable to search for new antitumor compounds. In this research, a promising medicinal chemistry strategy is molecular hybridization, which brings together two pharmacological entities and can bring great benefits to their bioactivity and toxicity. Combined with this strategy, computational chemistry tools, such as molecular docking, if well used, can optimize this process. In molecular docking, the affinity of a linker in a macromolecule is calculated, predicting its docking tendency in this target. The present study aimed the in silico evaluation of a library of hybrids and their intermediates with structures based on isatin and lapachol, as well as to synthesize the most promising compounds. The protein NADPH quinone oxidurredutase (NQO1) was chosen as the target protein because it is highly expressed in tumor cells. The AutoDock4 program was used in virtual screening by molecular docking. System validation was done by redocking the native ligand, and the RMSD was equal to 0.51. In general, all the dimers tested had an excellent antitumor potential against NQO1, with binding energies (EL) between -10 and -9 kcal/mol, same range as dicumarol (36), being 31a-31c and 35a-35c more promising, with EL in the range of -11 kcal/mol, just like the native E6A ligand (28). For the production of dimers, lapachol was extracted by Soxhlet and acid-base extraction. Intermediates were synthesized according to literature protocols, but the use of microwaves was also tested. Lapachol was obtained pure with a better yield in Soxhlet extraction (0.76%) than the acid-base one (0.14%). The synthesis of lapachol dimers 31a-31c, 35a-35c and 33a-33c did not lead to the final products, only to intermediates 29 (67.2% yield), 30a (quantitative yield), and 32a-32c (11.69 %, 27.23% and 31.6% yield). In contrast, the isatin dimers 23a-23c and 26a-26c were synthesized in yields of 41, 29 and 20% for 23a-23c and 29.5%, 26% and 17%, respectively, for 26a-26c. Intermediates 22a-22c were produced in 50% yield. The perspective is that these isatin homo and heterodimers 23a-23c and 26a-26c as well as the potentially active intermediates 32a-32c and 29 have their syntheses optimized and sent for in vitro tests of antitumor activity in order to confirm their potential and to relate the data obtained in silico and in vitro.